Penurunan Kadar COD Air Limbah Domestik Menggunakan Fly Ash dengan Metode Adsorpsi - Riztu, Sonia; Pradita, Natania Anggreani; Sufra, Rifqi; Adriansyah, Endi; P.T.Z, Luter evons; Suzana, Asih; Satria, Arysca Wisnu; Sanjaya, Andri (Universitas Batanghari Jambi, 2024)
Domestic wastewater was collected from a drainage system on Soekarno Hatta Street, Kalibalau Kencana, Kecepatan District, Bandar Lampung City, with a high Chemical Oxygen Demand (COD) content of 4,867 mg/L. If the wastewater is discharged directly into water bodies, it can reduce the availability of dissolved oxygen, potentially disrupting the survival of aquatic organisms. This research aims to determine the effect of contact time on the reduction of COD levels in domestic wastewater, the effect of fly ash adsorbent both activated and non-activated on the reduction of COD values, and its impact on other parameters according to domestic wastewater quality standards. Fly ash was activated using 6M NaOH and heated at 160°C for 1 hour. The adsorption process was carried out with varying contact times of 30, 60, 90, 120, and 150 minutes, using both activated and non-activated adsorbents with masses of 1.5 and 3 grams. The results of this study showed that the adsorption test with the activated adsorbent with masses of 1.5 and 3 grams reached optimum times of 90 and 60 minutes, respectively, with percentage reductions of 98.78% and 99.03%. In contrast, for the non-activated adsorbent with masses of 1.5 and 3 grams, optimum times occurred at 150 minutes, with percentage reductions of 95.64% and 90.79%, respectively.